A Multi-User Mobile GIS Solution for Documenting Large Surface Scatters: An Example from the Doring River, South Africa. (17th August 2020) - Ames, Christopher J. H.; Shaw, Matthew; O'Driscoll, Corey A.; Mackay, Alex
ABSTRACT: This article discusses the development and implementation of a mobile GIS catch-and-release system for documenting large surface artifact scatters along the Doring River in South Africa. An integrated, cloud-based mobile GIS solution was built using a suite of ESRI ArcGIS applications with an aim to maximize the speed and breadth of techno-typological data capture, while minimizing data collection errors and post-processing requirements. The system was successfully implemented during the 2019 field season of the Doring River Archaeological Project. With the ability for project-specific customization and interchangeable hardware components, the system transcends geographic region and temporal focus. Moreover, the system accommodates connectivity limitations commonly faced by archaeologists seeking distributed database solutions. Other challenges embraced in the design include rotating personnel throughout a field season, scalability without large financial investment, and the ability to accommodate data collection needs of other components of the larger multi-disciplinary research project.